A self-supervised vision transformer to predict survival from histopathology in renal cell carcinoma: original article - Wessels, Frederik; Schmitt, Max; Krieghoff-Henning, Eva; Nientiedt, Malin; Waldbillig, Frank; Neuberger, Manuel; Kriegmair, Maximilian; Kowalewski, Karl-Friedrich; Worst, Thomas; Steeg, Matthias; Popovic, Zoran V.; Gaiser, Timo; et al. (World journal of urology, 2023)
To develop and validate an interpretable deep learning model to predict overall and disease-specific survival (OS/DSS) in clear cell renal cell carcinoma (ccRCC).
Online veröffentlicht: 29. Juni 2023
Gesehen am 08.04.2024